2011
DOI: 10.1021/nn203969b
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Light-Driven Motorized Nanocar: Synthesis and Initial Imaging of Single Molecules

Abstract: A second generation motorized nanocar was designed, synthesized, and imaged. To verify structural integrity, NMR-based COSY, NOESY, DEPT, HSQC, and HMBC experiments were conducted on the intermediate motor. All signals in (1)H NMR were unambiguously assigned, and the results were consistent with the helical structure of the motor. The nanocar was deposited on a Cu(111) surface, and single intact molecules were imaged by scanning tunneling microscopy (STM) at 5.7 K, thereby paving the way for future single-mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
116
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(117 citation statements)
references
References 29 publications
0
116
0
1
Order By: Relevance
“…A key aspect of fulfilling the potential of synthetic rotary molecular motors for future applications in, e.g., molecular transport 42 and as tools for rotating objects much larger than themselves, 43 is reaching high rotational frequencies under ambient conditions. 24,44 A major experimental effort has therefore been invested in accelerating the rate-limiting thermal steps of overcrowded alkene-based rotary molecular motors, 18,19,21,[23][24][25]27,28,33 exploring the influence of conformational, steric and electronic factors.…”
Section: Methodsmentioning
confidence: 99%
“…A key aspect of fulfilling the potential of synthetic rotary molecular motors for future applications in, e.g., molecular transport 42 and as tools for rotating objects much larger than themselves, 43 is reaching high rotational frequencies under ambient conditions. 24,44 A major experimental effort has therefore been invested in accelerating the rate-limiting thermal steps of overcrowded alkene-based rotary molecular motors, 18,19,21,[23][24][25]27,28,33 exploring the influence of conformational, steric and electronic factors.…”
Section: Methodsmentioning
confidence: 99%
“…[23] Furthermore, while molecular motors are generally synthesized and tested in solution, a number of studies have demonstrated that many overcrowded alkenes maintain their rotary function also when attached to inorganic surfaces, [25,[36][37][38] which is widely regarded a key step in exerting control of the motors in future nanodevices. In other developments, overcrowded alkenes have been used as motors for propelling so-called nanocars along surfaces, [24,[39][40][41] thus effectively transforming their rotary motion into translation. In one such design shown in Figure 2, a rotary motor propels a nanocar with four C 60 wheels.…”
Section: R Ota R Y M Ol Ecu L a R Mot Orsmentioning
confidence: 99%
“…1c), one of a family of nanovehicles, termed nanocars. [24][25][26] The use of only one motor per vehicle eliminates the need for chiral resolutions in the synthesis since each motor has only one sense of possible rotary motion. Thus, opposing directional forces that can hinder translation in the case of two or more motors, as observed previously, 18 are avoided.…”
Section: Resultsmentioning
confidence: 99%